Design of a smart indoor air quality monitoring wireless sensor network for assisted living - Preethichandra, D. M. G. (2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2013)
Wireless indoor air quality monitoring is the main objective of this research in order to provide real time information for assisted living. The indoor air quality measured in the built environment provides a continuous stream of information for seamless controlling of building automation systems, and provides a platform for informed decision making. Further, this low power sensor network design provides vital air quality information under emergency and hazardous conditions even without grid power for a reasonable time. The proposed system has carbon dioxide, carbon monoxide, propane and methane sensors. This prototype network was first built using a hardware platform available in the market with industrial grade gas sensors. The concept was verified with actual parameter measurements under different real life situations. The results reveal that the domestic indoor air quality may be extremely different compared to what is expected for a quality living environment.